2023
DOI: 10.2355/isijinternational.isijint-2023-046
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Formed Coke for Blast Furnace Using Kraft Lignin as a Binder

Hiroshi Nonaka,
Takahiro Tomono,
Yoshihiro Nagashima
et al.

Abstract: In the steel industry, the development of a coke production technology that uses low-grade coal is desired. Decarbonization by the use of plant biomass is also an important option. A candidate is formed coke, which is produced by forming non-coking coal using a binder, followed by carbonization. Kraft lignin, by-product in pulp and paper mills is a potential binder because it is an aromatic polymer dissolved from wood. In this study, thermal coal powder was blended with softwood kraft lignin powder at ratios f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…However, the share of substitutable coal has been 2-10%. In their recent article, Nonaka et al 7) used kraft lignin as a binder in coke and found that the tensile strength of coke reached a maximum at 10% lignin content. From a metallurgical perspective, the main concerns are the lower CSR value (coke strength after reduction) and higher CRI value (coke reactivity index).…”
Section: Effect Of Biocarbon Addition On Metallurgical Properties Of ...mentioning
confidence: 99%
“…However, the share of substitutable coal has been 2-10%. In their recent article, Nonaka et al 7) used kraft lignin as a binder in coke and found that the tensile strength of coke reached a maximum at 10% lignin content. From a metallurgical perspective, the main concerns are the lower CSR value (coke strength after reduction) and higher CRI value (coke reactivity index).…”
Section: Effect Of Biocarbon Addition On Metallurgical Properties Of ...mentioning
confidence: 99%
“…Numerous studies have demonstrated that replacing or partially replacing bentonite with organic binders is feasible. However, due to their high cost and thermal instability, they are not widely utilized [8][9][10][11] . The use of low-cost solid waste as binder raw materials is also a research hotspot.…”
Section: Introductionmentioning
confidence: 99%